Association between blood lead levels and constipation in adults: insights from NHANES data (2005–2010) - Yue-Juan Li; Hui Dong; Wen-Xing Chen; Deng-Chao Wang; Miao Yu (BMC Gastroenterology)
Abstract Background Constipation is a common health issue affecting quality of life. While environmental factors like lead exposure may influence gastrointestinal function, the link between blood lead levels and constipation is underexplored. This study, based on NHANES data, investigates the association between blood lead levels and constipation prevalence in adults. Methods This study analyzed NHANES data from adults aged 20 years and above, collected between 2005 and 2010. A multivariable logistic regression model was used to assess the association between blood lead levels and constipation prevalence, adjusting for potential confounders such as age, gender, and race. Restricted cubic spline (RCS) regression was used to explore the nonlinear trends in the association between blood lead levels and constipation, and subgroup analyses were conducted to examine potential interactions among subgroups. Results A total of 13,992 adults were included in the analysis. The results showed a significant inverse association between blood lead levels and the prevalence of constipation after full adjustment for potential confounders (Model 3) (OR: 0.92, 95% CI: 0.86–0.98; P = 0.02). Quartile analysis also revealed that participants in the Q4 group had a significantly lower odds of having constipation compared to those in the Q1 group (OR: 0.70, 95% CI: 0.53–0.93; P = 0.01). RCS analysis confirmed a nonlinear inverse association between blood lead levels and the prevalence of constipation (nonlinearity P < 0.01). Subgroup analyses did not reveal any significant interactions. Conclusion This study demonstrates that higher blood lead levels are associated with a lower prevalence of constipation, contradicting traditional views. This may suggest a complex mechanism of lead’s impact on gastrointestinal function. Future research should further explore the causal relationship and potential biological mechanisms between blood lead and constipation.